2020
DOI: 10.1177/0960327120913094
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of luteolin against lead acetate-induced cortical damage in rats

Abstract: Luteolin (LUT) is a glycosylated flavonoid compound that has multiple beneficial pharmacological and biological impacts. The current investigation was undertaken to evaluate the putative neuroprotective potency of LUT against neuronal damage induced by lead acetate (PbAc). Twenty-eight rats were placed into four equal groups. Group 1: served as the control group, group 2: rats were supplemented orally with LUT (50 mg kg−1), group 3: rats were intraperitoneally injected with PbAc (20 mg kg−1), and group 4: rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 46 publications
(49 reference statements)
1
26
0
Order By: Relevance
“…High levels of ROS lead to oxidation of the cellular biomolecules, especially, the biomembrane lipids causing lipid peroxidation 44 . These results are agreed with the previous studies 18,26,32,36,45 . Inflammation is considered as a beneficial process under normal condition via controlling the innate response to biological or physical triggers such as trauma, infection and other pathogens that may disrupt homeostasis and cause diseases 46 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…High levels of ROS lead to oxidation of the cellular biomolecules, especially, the biomembrane lipids causing lipid peroxidation 44 . These results are agreed with the previous studies 18,26,32,36,45 . Inflammation is considered as a beneficial process under normal condition via controlling the innate response to biological or physical triggers such as trauma, infection and other pathogens that may disrupt homeostasis and cause diseases 46 .…”
Section: Discussionsupporting
confidence: 94%
“…The brain is the most critical organ for lead toxicity 9 . Both of the PNS and the CNS are affected by lead toxicity 19 but, the mechanisms of lead neurotoxicity are complex and still not clearly understood 17,32 . However, in adults, the PNS is more affected, while in children, the CNS is more affected 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Lead has a high affinity for thiol groups or metal cofactors in enzymatic and non‐enzymatic antioxidants and molecules, the binding of which results in a decline in antioxidant enzyme activities, including SOD, CAT, GPx, and GR activities (Baty et al., 2020). Our experimental findings are in accordance with those of AL‐Megrin, Soliman, et al (2020), who reported a prominent elevation in hepatic MDA levels and a marked depletion in enzymatic and non‐enzymatic antioxidants and molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Baty et al. (2020) revealed that activation of the caspase cascade and concurrent extracellular signal‐regulated kinase dephosphorylation is the most operative pathway directly associated with apoptotic signals triggered by PbAc in vivo. Caspase‐3 hyperactivity can induce DNA breakage, chromatin condensation, and apoptosis of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…45 Luteolin can suppress neuroinflammation through several mechanisms, including decreasing the release of cytokines/chemokines, NO, reactive oxygen species (ROS), protein kinase C (PKC), Ca ++ influx, and inhibiting Akt, and nuclear transcription factor-κB (NF-κB) in SH-SY5Y human neuroblastoma cells in vitro. 27,46,47 Additionally, luteolin can suppress the activation of NF-kB, signal transducer and activator of transcription 3 (STAT3), c-Jun N-terminal kinases (JNK), p38, and extracellular signal-regulated kinases 1/2 (ERK1/2) that are involved in the glial cell activation and inflammatory mediator release. 48 Neurotrauma is a known risk factor for neurodegenerative diseases through TBIassociated secondary injury, and luteolin administration can protect from these neurodegenerative diseases.…”
Section: Neuroprotective Effects Of Luteolin In Neuroinflammatory Dmentioning
confidence: 99%